INTRODUCTION OF THE CHERRY GENE POOL IN THE NORTHERN ENVIRONMENTS OF THE RUSSIAN FEDERATION AND THE RESULTS OF ITS STUDYING FOR 50 YEARS - A. A. Yushev; S. Yu. Orlova (Труды по прикладной ботанике, генетике и селекции)
The cherry collection maintained at Pavlovsk Experimental station of VIR has been studied since 1967 in the context of the dynamics of newly acquired accessions. The main goal was to identify sources of the highest winter hardiness, frost tolerance and resistance to harmful diseases, such as cherry leaf spot and brown rot of the fruit, as well as other biological and economic traits valuable for breeders, such as self-fertility or large fruit size. Many years of research have resulted in identifying genotypes with different levels of field resistance in the years with average and epiphytotic type of disease development, and with the best indices of biological and economic traits.